Fabrication and Characterization of Light-responsive Multilayer Films of Chitosan and Azopolymer. (2015) - Fernández, Raquel; Gutierrez, Junkal; Eceiza, Arantxa; Tercjak, Agnieszka
Abstract: Photoresponsive multilayer films consisting of alternating layers of chitosan and an azopolymer were developed by layer-by-layer self-assembly. The influence of the pH and the number of bilayers on the structure and properties of the films was investigated by different experimental techniques.